Genetic analysis of F2 and transgressive segregants for seed yield in safflower (Carthamus tinctorius L.) - D.Shivani, Ch. Sreelakshmi and C.V. Sameer Kumar (Electronic Journal of Plant Breeding, 2011)
The wide range of F2 variability for seed yield, number of capitula per plant and number of seeds per capitulum in 24 crosses ofline x tester set indicated potential of the crosses to throw large number of variable segregants. Maximum number of positivetransgressive segregants was found in TSF-1 x SFS 9920, TSF-1 x SSF 658, TSF-2 x ASD-07-10, Sagarmutyalu x SFS 9920andManjira x SSF 698 crosses. F1 per se performance, relative heterosis, D2 and GCA effects of parents were found to be goodindicators for predicting the phenotypic variance and genetic advance for seed yield in F2. Average GCA effects of parents hadmoderate degree of influence on the mean of 10% top yielding plants in F2.